Caracterização da dinâmica espectro temporal florestal e da cana-de-açúcar no município de Itapemirim, ES - Magalhães, Ivo Augusto Lopes (2013)
We use the spectral response of vegetation with the intent to discriminate biophysical parameters, constituent material, the cell structure of the leaves and photosynthetic activity. In this context the purpose of this study was to characterize and compare the spectral signatures of the targets: seasonal forest, submontane, cane sugar, ground, urbanization and water body located in the municipality of Itapemirim, ES, using data from the Thematic Mapper sensor but also to analyze the dynamics of vegetation through Vegetation Index Normalized Difference - NDVI for the years 1984 to 2011. The methodology consisted in obtaining the images through the electronic catalog from INPE. The images went through a Digital Image Processing methodological expressed in the following sequence: Mosaic, registration, atmospheric correction, conversion to bidirectional reflectance and NDVI's finally image. We used the nonparametric Wilcoxon P-value with a 1% probability to distinguish the mean values of NDVI's differ statistically compared with submontane semideciduous forest and two plots of the same variety of cane sugar RB 86-7515 and SP 83- 3250. As a result we obtained the registration of the series with RMS less than 0.5 pixel. For the atmospheric correction was subtracted pixel spurious multitemporal images in all of the visible region the Near Infrared. The seasonal forest, submontane and cane sugar showed typical spectral responses of vegetation, with low reflectance value in the region of blue and red, with a high value in the region of IVP. The body fluid did not show a spectral curve of a typical pure water having a high spectral response in the red and green bands, from the presence of macrophytes and suspended solids. In urban areas obtained a high reflectance in the red region, and attributed the significant presence of exposed soil, unpaved streets and homes with a significant amount of tiles and clay bricks. It was found by analyzing multitemporal NDVI was possible to analyze the vegetation dynamics, gain, loss of green biomass, and phenological cycle management of varieties of cane sugar.